"Early Trigger" Intravenous Vitamin K: Optimizing Target-Driven Care in Warfarinised Patients With Hip Fracture. (December 2015) - Diament, Marina; MacLeod, Kirsty; O'Hare, Jonathan; Tate, Anne; Eardley, Will
Best practice tariff (BPT) was introduced as a financial incentive model to improve compliance with evidence-based care, such as operation for hip fracture within 36 hours of admission. We previously evaluated the impact of warfarin on patients with hip fracture, revealing significant delay to operation and subsequent loss of revenue. As a result of this, an "early trigger" intravenous vitamin K (IVK) pathway was introduced and the service reaudited a year later. The first cycle was a retrospective audit of all cases with hip fracture against BPT standards over a 32-month period. Subsequent protocol change resulted in all warfarinised cases being given 2 mg IVK in the emergency department prior to blood testing. This protocol was reaudited against the same BPT standards 12 months later. An intention-to-treat approach was used, despite breaches of protocol and other reasons for patients not progressing to theater. The data were analyzed with parametric tools to establish true clinical and statistical impact of the introduction of the protocol. In the first cycle, 80 patients were admitted on warfarin with a mean time to theater of 53.71 hours. Of these patients, 79% breached BPT due to anticoagulation. Twelve months following protocol introduction, 42 patients had a mean time to theater of 37.61 hours. Of these patients, 34% breached BPT due to anticoagulation. These data are both clinically and statistically significant ( P < .001). No adverse events occurred. We have shown for the first time that "early-trigger" IVK can reduce delay to theater and maximize tariff payments in warfarinised patients with hip fracture. This is in addition to other established benefits associated with early surgery such as decreasing risk of pressure lesions and pneumonia. It affords high-quality patient-centered care while ensuring trauma units achieve maximal financial reimbursement through pay for improved performance and supports a culture of change behavior.